Comparing Virtual Reality and 2-Dimensional Drawings for the Visualization of a Construction Project - Calderon-Hernandez, C (2019)
This work was partially funded by the Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica del Perú (CONCYTEC from its acronym in Spanish), according to the Convention N° 232-2015-FONDECYT. The team would like to thank Brasfield & Gorrie for granting us access to the BIM models of the project. However, the opinion presented herein does not necessarily reflect theirs. Finally, the authors want to thank So Yoon Yoon, for allowing us to use the revised version of the PSVT: R for this study.